Influence Of Cash Flow, Capital Structure, Operational Costs and Capital Intensity Towards Corporate Income Tax Payable - Handayani, Puspita; Cantika Rila Zety, Wita (EAJ (Economic and Accounting Journal), 2024)
This research aims to analyze the influence of Cash Flow, Capital Structure, Operational Costs and Capital Intensity. The theory used in this research is agency theory. The approach used in this research is a quantitative approach. The research method uses panel data analysis with E-views12 software to test random effect and fixed effect models, and determine the most relevant model through the Chow Test and Hausman Test. This research includes data from manufacturing companies in the property and real estate subsector listed on the Indonesia Stock Exchange, which publish complete annual financial reports in rupiah during the 2018-2023 period, as well as companies that experienced profits during that period. Of the total 92 companies that met the criteria for this research, 11 were companies. It is hoped that the results of this research can contribute to improving the quality of financial information and understanding of accounting conservatism in Indonesia. The data analysis technique used is descriptive statistics. The results of this research are that Cash Flow, Capital Structure, Operational Costs have no effect on Corporate Income Tax Payable and Capital Intensity has an effect on Corporate Income Tax Payable.